Can rationing increase welfare? Theory and an application to India's ration shop system - Lucie Gadenne (Institute for Fiscal Studies (IFS), 2018)
Ration shop systems allow households to purchase limited quantities of some commodities at a fi xed subsidized price and are in widespread use throughout the developing world. I construct a model of piece-wise increasing commodity taxation to consider whether the use of ration shops can be rationalized by the characteristics of developing countries: limited government capacity to observe household incomes and high commodity price risk. I find that an efficiency-maximizing government will never use ration shops but a welfare-maximizing one might, to redistribute and provide insurance. Welfare gains from introducing ration shops are highest for necessity goods with high price risk. Calibration results for India suggest that ration shops are welfare improving relative to a universal transfer scheme for three of the four goods sold through the system today. Welfare gains are wiped out however once more than 6% of the funds allocated to ration shops are lost to corruption or administrative costs.
Keywords: 330